Protein utilization responses of growing pigs to supplemental lysine as liquid versus crystalline forum in barley-barley protein diet - Näsi, Matti (Agricultural Research Centre of Finland, 1992)
Tutkimuksessa selvitettiin nestemäisen ja kiteisen puhtaan lysiinin lisäysten vaikutusta ohra-ohravalkuaisdieetillä ruokittujen lihasikojen valkuaisen hyväksikäyttöön. Tutkimus tehtiin 8 x 8 latinalaisella neliönä 30-100 kg elopainoisilla lihasioilla. Rehun raakavalkuaispitoisuus oli kaikissa kahdeksassa koerehuseoksessa sama 160 g/kg. Lysiinitäydennykset olivat 1, 2 ja 3 g/kg puhtaana lysiininä kumpaakin lysiinilähdettä käytettäessä. Seosten kokonaislysiinipitoisuudet olivat 5.5 g/kg täydentämättömässa seoksessa ja vastaavasti 6.5, 7.5 ja 8.5 g/kg täydennetyissä rehuseoksissa. Vertailuseoksena oli soija-ohraseos, jossa oli 7.4 g/kg lysiiniä. Lysiinilisäyksellä verrattuna täydentämättömään dieettiin oli merkitsevä vaikutus moniin valkuaisen hyväksikäyttöä kuvaaviin tunnuslukuihin. Lysiinin lisääminen paransi lineaarisesta typen pidättymistä ja valkuaisen biologista arvoa sekä vähensi virtsan typen ja urean eritystä. Sikojen typpitase parani keskimäärin 10 % lisättyä lysiiniä g/kg kohti. Lysiinilähteiden välillä ei ollut eroa. Soija-ohraseoksella ruokittujen sikojen ja vastaavalla lysiintasolla olleiden ohra-ohravalkuaisella ruokittujen sikojen valkuaisen hyväksikäytössä ei ollut eroja. Tutkimuksen tulosten mukaan lysiinitäydennyksellä voitiin viljavalkuaisen biologista arvoa parantaa samaan tasoon kuin viljan ja soijan seos.

The study examined the influence of increasing dietary supplements of liquid compared to crystalline lysine on nitrogen (N) balance and protein utilization in growing pigs (30-100 kg LW) in a 8*8 Latin square. Eight isonitrogenous diets with 160 g CP/kg were formulated from barley and barley protein supplemented with the two lysine sources at levels of none, 1, 2 and 3 g/kg to provide 5.5, 6.5, 7.5 and 8.5 g/kg total dietary lysine. Barley-SBM served as a control diet. The dietary lysine concentration had substantial effect on N retention and metabolism. The lysine supplements to the cereal-based diet with a low lysine content, 5.5 g/kg, significantly improved N-retention, decreased urinary-N excretion and enhanced protein utilization and daily gain. There was a linear response of N-retention, urinary-N and urea-N excretion and apparent biological value (P<0.001) to lysine supplementation level. As the lysine concentration was gradually increased, the efficiency of N retention in relation to N intake and absorbed N increased Iinearily. No difference was found in N balance parameters between the two lysine sources, liquid vs. crystalline form being equal in their response. Pigs fed the SBM-diet compared to the barley protein diet fortified with lysine did not differ in response of N retention and protein utilization, but SBM lead to lower urinary-N excretion. N retention, urinary-N excretion and biological value as parameters for protein utilization showed lower variability (CV 0.08-0. 1 0) compared to urinary urea-N excretion (CV 0.20). Regression coefficients of responses of protein utilization to liquid lysine were overall lower than those to crystalline lysine.
Keywords: Ko; sika; lysiini; aminohapot; valkuaisrehut; rehut; ruokinta; lysine; pure amino acid; protein; nitrogen balance; pig